Small Airway Dysfunction Affects One in Five Indian Adolescents: The Multicity APEAL Study - Mohammed Kaleem Ullah; Anant Mohan; Rajesh Kumar Thimmulappa; Harish Chandra Phuleria; Santu Ghosh; Rajesh Majumder; Swapnali Patil; Priya Samdarshi; Sathish Chandran Mayigaiah; Ashwaghosha Parthasarathi; Jayaraj Biligere Siddaiah; Twinkle Agrawal; et al. (Clinical & Experimental Allergy, 2026)
Summary Small airway dysfunction affected one in five adolescents and varied substantially across four Indian cities. Age, sex and study city, but not ambient PM 2.5 or NO 2 , were independently associated with FEF 25–75 .